Comparison of Several Processing Methods in Preserving the Flavor Properties of Andaliman (Zanthoxylum acanthopodium DC.) Fruit - Florensia Irena R. Napitupulu; Christofora Hanny Wijaya; S. Sulistiyani; Endang Prangdimurti; Clarissa Akyla; Lisa Amanda Yakhin; Susi Indriyani (Journal of Engineering and Technological Sciences, 2020)
Andaliman (Zanthoxylum acanthopodium DC.) is a plant endemic to North Sumatra. Its fruit has a very specific citrus-like aroma, gives a tingling sensation and is commonly used for seasoning in Bataknese traditional cuisine. To extend the shelf life and preserve the quality of andaliman fruit, post-harvest handling is needed. Seven drying methods were applied and compared, i.e. sun, air, fluidized bed, oven, far infrared, freeze, and spray drying. Considering the physicochemical and sensory properties and efficiency, oven drying was selected for further study. The optimum condition for drying was temperature at 54 °C for 8 h resulting in 0.67 desirability level based on the response surface method (RSM). Spray drying encapsulation of andaliman fruit extract was performed at an inlet temperature of 150 °C with an extract to carrier ratio of 1:8. Maltodextrin (MD) and gum arabic (GA) with a ratio of 3:2 was chosen as the carrier agent. The quantitative descriptive analysis (QDA) result showed that the encapsulated andaliman powder had a flavor that resembled fresh andaliman with a more pronounced taste, a citrus-like trigeminal sensation, and a sour floral citrusy aroma.